A process for embedding fiber Bragg gratings in flexible skin foils - Silva, A. F. (2010)
Optical fiber sensors are increasingly used for monitoring purposes, but flexible smart structures based in this type of technology have many industrial applications. This paper explores a new approach for integrating optical fiber sensors in flexible substrates that can be mounted in host structures to monitor. This approach combines two well establish components, Fiber Bragg grating (FBG) sensors and flexible skin-foils. A three-layer foil construction based on the spread-coating process was defined, in which the fiber was embedded in the middle layer. Such disposition ensured protection to the optical fiber element without reducing the sensitivity to external stimulus. The functional prototypes were subject to thermal and mechanical tests, in which its performance was evaluated. The smart structure behaves linearly to temperature cycles by 0.01 nm/°C and is able to withstand high strain cycles without affecting the measurement characteristics. The obtained results validated this approach. In addition, the flexibility of the explored method allows custom fiber layouts, finishing patterns and colors, enabling this way a range of possible application fields.